Efficacy and safety of early cholecystectomy for comorbid acute cholecystitis and acute cholangitis: Retrospective cohort study. (February 2019) - Abe, Tomoyuki; Amano, Hironobu; Hanada, Keiji; Bekki, Tomoaki; Minami, Tomoyuki; Yonehara, Shuji; Noriyuki, Toshio; Nakahara, Masahiro
Abstract: Background: This study investigated the optimal timing and usefulness of early cholecystectomy for acute cholecystitis in patients with comorbid acute cholangitis. Materials and methods: In 2011–2016, 252 patients who underwent early cholecystectomy for acute cholecystitis and 7 who underwent delayed cholecystectomy were enrolled and compared. Patients with comorbid acute cholangitis were then divided into those who underwent urgent cholecystectomy (within 72 h after symptom onset), semi-urgent cholecystectomy (3–14 days after symptom onset), or delayed cholecystectomy (3 months after symptom onset). Results: There were no significant intergroup differences in postoperative complication rate ( p  = 0.561), operation time ( p  = 0.496), or intraoperative blood loss ( p  = 0.151) between those with and those without acute cholangitis. Postoperative stays were significantly longer in the comorbid acute cholangitis group ( p  = 0.004). In the patients with acute cholangitis, the urgent cholecystectomy, semi-urgent, and delayed cholecystectomy groups had comparable intra- and postoperative outcomes. Conclusion: Early cholecystectomy within 14 days after symptom onset was safely performed for patients with concomitant acute cholecystitis and acute cholangitis after the successful treatment of acute cholangitis. Highlights: Feasibility and safety of early cholecystectomy for concomitant acute cholecystitis with acute cholangitis within 14 days after symptom onset. Upfront treatment for acute cholangitis is essential for achieving low postoperative mortality in case of concomitant acute cholecystitis and acute cholangitis.